Pengaruh Ketidakpastian Lingkungan, Sistem Pengukuran Kinerja, dan Gaya Kepemimpinan Terhadap Kinerja Manajerial UMKM Kuliner di Surakarta - Rachel Angel Maharani; Hudi Kurniawanto (Pusat Riset dan Inovasi Nasional, 2026)
The purpose of this study is to examine how leadership style, performance evaluation tools, and environmental uncertainty affect managerial performance in Surakarta City's culinary MSMEs. MSMEs are an important industry.supporting the local economy, yet they struggle to continue managing effectively in a corporate environment that is always changing. 133 culinary MSMEs were given questionnaires as part of this study's quantitative survey methodology. The method of data analysis that was employed was multiple linear regression. The study's findings demonstrate that managerial performance is positively and significantly impacted by environmental uncertainty, positively and significantly impacted by the performance measurement system, and positively and significantly impacted by leadership style. The performance measurement system and leadership style contribute significantly to managerial effectiveness, while adaptability to environmental uncertainty is a key supporting factor. Therefore, to increase business competitiveness and sustainability, MSMEs need to strengthen structured performance measurement systems and evaluate them regularly, implement participatory leadership styles and human resource development, and enhance their ability to adapt to the dynamics of the business environment.